Efektivitas Kombinasi Ekstrak Etanol Daun Bunga Matahari dan Tanaman Anting-Anting sebagai Antimalaria Secara In Vivo: Effectiveness of Ethanol Extract Combinations of Sunflower (Helianthus annuus) Leaves and Anting-anting (Acalypha indica Linn) as In Vivo Antimalarial - Ngibad, Khoirul (Universitas Tadulako, 2019)
Sunflower (Helianthus annuus) and anting-anting (Acalypha indica Linn), can be studied as efficacious malaria medicinal plants for preventing the development of malaria plasmodium resistance. This study aims to determine the effectiveness of the combination of 80% ethanol extract of sunflower leaves and anting-anting as antimalarials. This study included extraction of sunflower leaves and anting-anting plant separately using the maceration method for 24 hours with 80% ethanol. Stirring is aided by a 3 hour shaker and then the obtained extracts were mixed and tested in vivo antimalarial activity against mice test animals. Data of the parasitemia degree was analyzed for the determination of Effective Dose (ED50) using probit analysis then determination of Combination Index (CI) value. The results of the antimalarial activity test on tested mice were ED50 of 1.23 mg/kg human body with a Combination Index (CI) of 0.46 (CI <1) which means synergistic potency.